Los juegos recreativos para el desarrollo del lenguaje oral de los párvulos con necesidades educativas especiales - Ramírez Granja, Claudia Inés (2022)
Language constitutes an important function for all human beings, because through it it is possible to understand the world and interact with everything around it, in addition to being an essential element to be able to learn; during the early childhood education stage, its stimulation is essential as it will help the child to develop in a better way. However, those who have special educational needs are not always stimulated in an ideal way from the classroom, which makes their language development processes occur more slowly, causing pedagogical delays. Due to the importance that this has, it was decided to carry out the present study, in which it was possible to carry out an analysis of how recreational games can contribute to developing oral language in these students, since playful activities usually cause motivation; For this, a descriptive field investigation was developed, in which teachers from the "Tía Uchy" Child Development Center, DECE staff and students were used as a sample, obtaining as main results the lack of use of recreational games. to stimulate oral language, so a guide for teachers is proposed with the aim of promoting this end.